Frontline Clinician Knowledge of Antimicrobial Prescribing in an Academic Tertiary Children's Hospital: A Point Prevalence Study. (11th May 2015) - Larru, Beatriz; Sulieman, Salwa E.; Localio, Russell; Ross, Rachael K.; Sharland, Mike; Zaoutis, Theoklis E.; Gerber, Jeffrey S.
Abstract: Frontline clinicians caring for hospitalized children typically knew the indication for antimicrobial therapy but less often knew the current day or planned duration of therapy or of plans for intravenous to oral conversion. Night shift clinicians were less likely to know day of therapy and duration of therapy than day shift clinicians caring for the same patients.